Vulnerable young women and frontline service providers identify options to improve the HIV-sensitivity of social protection programmes in Botswana: A modified Policy Delphi approach - Ran van der Wal; Miriam Kobo; Anne Cockcroft; Isabelle Vedel; Mira Johri; Neil Andersson (Taylor & Francis Group, 2023)
Poverty, lack of education and gender inequality make unemployed and out-of-school young women extremely vulnerable to HIV infection. Promotive social protection programmes aim to increase livelihood and capabilities and could empower this priority population to act on HIV prevention choices. In Botswana, they rarely benefit from such programmes. A modified Policy Delphi engaged a panel of 22 unemployed and out-of-school young women and eight frontline service providers to consider alternative policy and practice options, and tailor available programmes to their own needs and social situation. The panel assessed the desirability and feasibility of improvement proposals and, in a second round, ranked them for relative importance. Nearly all 40 improvement proposals were considered very desirable and definitely, or possibly, feasible, and panellists prioritised a wide range of proposals. Frontline service providers stressed foundational skills, like life skills and second chance education. Young women preferred options with more immediate benefits. Overall, panellists perceived positive role models for programme delivery, access to land and water, job skills training, and stipends as most important to empower HIV-vulnerable young women. Results suggest ample policy space to make existing social protection programmes in Botswana more inclusive of unemployed and out-of-school young women, hence more HIV-sensitive.